ADDED VALUE ANALYSIS: AVOCADO PRODUCTION IN PIECES - García Z., Teonila (2003)
This work seeks to set Avocado's Value Added through Chopped- Avocado Production, from actual information on raw material characteristics, product quality requirements, national production, actual markets and both national and international trade, with the purpose of proposing a project's engineering based on a suitable industrial process and the required resources.